Pengaruh Literasi Keuangan dan Perilaku Keuangan terhadap Keputusan Investasi Mahasiswa Kota Bandung - Rizki Sobari; Amilia Tresnawati (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to evaluate the level of financial literacy and financial habits that influence investment decisions among university students in Bandung City. The information collection procedure used was by distributing questionnaires to research participants. A total of 123 respondents were successfully collected for this research. The approach used in this research is descriptive quantitative. Analysis was attempted using multiple linear regression tests with the use of the SPSS 23 program. The results show that the level of financial literacy and financial behavior of university students in Bandung tends to lie at the good and medium levels. Not only that, the findings show that the level of financial literacy and financial attitudes significantly influence the investment decisions of university students in Bandung. From these results, it can be concluded that the better the level of financial literacy and financial behavior of a person, the better his investment decisions tend to be.